Genealogies of recovery: The framing of therapeutic ambitions. (20th October 2017) - Brown, Brian; Manning, Nick
Abstract: The notion of recovery has become prominent in mental healthcare discourse in the UK, but it is often considered as if it were a relatively novel notion, and as if it represented an alternative to conventional treatment and intervention. In this paper, we explore some of the origins of the notion of recovery in the early 20th century in movements such as Alcoholics Anonymous and Recovery Inc. Whilst these phenomena are not entirely continuous with recovery in the present day, some important antecedents of the contemporary notion can be detected. These include the focus on the sufferers' interior space as a key theatre of operations and the reinforcement and consolidation of medical ways of seeing the condition without any immediate medical supervision of the actors being necessary. This has resonance with many contemporary examples of recovery in practice where the art of living with a mental health condition is emphasised without the nature of the psychopathological condition itself being challenged.